GENERAL CONSIDERATIONS OF JUDICIAL WILL REGARDING ITS LIMITS IN ECO – ECONOMICAL CONTRACTS - MIHAELA C. PAUL (MODREA); IOSIF R. URS; IUDITH IPATE (Challenges of the Knowledge Society)
After a brief study of the contract legal concept we attempted to examine the essential elements of the contract - the agreement of will between parties. The autonomy theory of will - which legally promoted contemporary, the concept of freedom of contract, we will analyze the concept in question, both over time and in last centuries when transformations of freedom of contract and contractual law have been most reliable, amplifying the ambiguity of the meaning of contractual freedom in the Romanian legal order and the number and diversity of doctrines that were interested in freedom of contract become substantial. Economic and social realities experienced significant changes, which made the autonomy theory of will first to be put in question and then challenged, attempting to detect the judicial construction of the contract.